(untitled) (Journal of Engineering, 2023)
Zinc Oxide is an indispensable substance in the field of dental treatment. It is used daily and intensively in all governmental and private dental clinics, leading to the disposal of very high concentrations of zinc with waste and eventually in landfill sites as a final destination for solid waste removal. This indicates the urgent need to investigate its behavior upon disposal due to the surrounding conditions. Approximately 4195 g of mixed dental waste samples were collected from (17) healthcare centers in Baghdad Al-Karkh. The leaching behavior of ZnO powder was investigated through batch reactors using makeup dental solid waste samples. The ZnO leaching was tested with 3 conditions; acidic, alkaline, and Ionic Strength (IS). The acidic condition was considered the most hazardous condition compared with basic and salinity due to the increasing tendency of ZnO to release Zn ion within waste leachate. In solutions with low pH, the dissolution of ZnO tends to produce zinc ions due to the attack of the ZnO surface by proton. In solutions of pH more than 9, the degradation of zinc oxide produces hydroxide complexes. Increasing (IS) decreased zinc concentration in leachate samples with time by promoting solids aggregation, decreasing the repulsive forces of ZnO particles, and accumulating in the bottom of reactors.